Copper(ii) coordination polymers: tunable structures and a different activation effect of hydrogen peroxide for the degradation of methyl orange under visible light irradiation. Issue 3 (26th November 2014) - Liu, Lu; Wu, Dongqing; Zhao, Bei; Han, Xiao; Wu, Jie; Hou, Hongwei; Fan, Yaoting
Abstract : By tuning reaction condition of Cu(ii )/btmx system, three Cu(ii ) coordination polymers were synthesized. Under visible light, 1–3 display different activation effect of hydrogen peroxide (H2 O2 ) in degrading methyl orange (MO). Abstract : By tuning the synthesis conditions, based on a conformation-sensitive ligand, 1, 4-bis(1, 2, 4-triazole-1-methylene)-2, 3, 5, 6-tetramethyl benzene (btmx) and Cu(NO3 )2 ·3H2 O/CuCl2 ·2H2 O, we have obtained three Cu(ii ) coordination polymers with diverse structures, namely, [Cu(btmx)2 (H2 O)]·2NO3 n (1 ), [Cu(btmx)2 (Cl)2 ]·5H2 O n (2 ) and [Cu(btmx)(Cl)2 ] n (3 ). Complex1 exhibits a novel 2D → 3D interpenetrating structure with a point symbol of 6 3 . Complex2 features an irregular 2D grid with (4 4 ·6 2 ) topology. The structure of complex3 is a 1D double chain structure. The ultraviolet-visible absorption spectra and TG curves of these complexes are also presented and discussed. Moreover, under visible light, the coordination polymers1, 2, and3 display a different activation effect of hydrogen peroxide (H2 O2 ) for the photocatalytic decomposition of methyl orange (MO), which indicates that the coordination polymers may have bright prospects in the field of photocatalytic degradation of dyes.